Respuesta :

gmany

[tex]\text{Use}\ \sqrt[n]{a^m}=a^{\frac{m}{n}}\ \text{and}\ a^{-1}=\dfac{1}{a}\\\\\dfrac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}=\left(x^{\frac{2}{7}\right)\left(\dfrac{1}{y^\frac{3}{5}}\right)=\left(x^{\frac{2}{7}}\right)\left(y^{-\frac{3}{5}}\right)[/tex]

Answer: [tex](x^{\dfrac{2}{7}})(y^{-\dfrac{3}{5}})[/tex]

Step-by-step explanation:

The given expression : [tex]\dfrac{\sqrt[7]{x^2}}{\sqrt[5]{y^3} }[/tex]

Law of radicals :-

[tex]\sqrt[n]{a}=a^{\frac{1}{n}}\\\\\sqrt[n]{a^m}=a^{\frac{m}{n}}[/tex]

Law of exponent:

[tex]\dfrac{1}{a^n}=a^{-n}[/tex]

Using the above law of radicals and law of exponent we have,

[tex]\dfrac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}\\\\=(x^{\frac{2}{7}})(y^{-\frac{3}{5}})[/tex]

ACCESS MORE